2022
DOI: 10.1093/cid/ciac925
|View full text |Cite
|
Sign up to set email alerts
|

Age and Cancer Incidence in 5.2 Million People With Human Immunodeficiency Virus (HIV): The South African HIV Cancer Match Study

Abstract: Background Old age is an important risk factor for developing cancer, but few data exist on this association in people with HIV (PWH) in sub-Saharan Africa. Methods The South African HIV Cancer Match study is a nationwide cohort of PWH based on a linkage between HIV-related laboratory records from the National Health Laboratory Services and cancer diagnoses from the National Cancer Registry for 2004-2014. We included PWH who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…This is consistent with the findings of Stelzle et al, who reported that women accounted for the majority of cervical cancer cases associated with HIV in Eastern and Southern Africa in 2018 3 . Cervical cancer is categorized as an AIDS‐defining illness, and it is more prevalent in women living with HIV, particularly in South Africa 24 . Studies has reported that more than half of women infected with HIV live in the East and South Africa, 25 and a maximum HPV prevalence ~20% in Africa females 26 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the findings of Stelzle et al, who reported that women accounted for the majority of cervical cancer cases associated with HIV in Eastern and Southern Africa in 2018 3 . Cervical cancer is categorized as an AIDS‐defining illness, and it is more prevalent in women living with HIV, particularly in South Africa 24 . Studies has reported that more than half of women infected with HIV live in the East and South Africa, 25 and a maximum HPV prevalence ~20% in Africa females 26 .…”
Section: Discussionsupporting
confidence: 91%
“…3 Cervical cancer is categorized as an AIDS-defining illness, and it is more prevalent women living with HIV, particularly in South Africa. 24 Studies has reported that more than half of women infected with HIV live in the East and South Africa, 25 and a maximum HPV prevalence ~20% in Africa females. 26 As a result, the Eastern and Southern Africa region was responsible for nearly 30% of all DALYs related to cervical cancer and attributable to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…32 Besides South Africa shouldering the heaviest burden of HIV-related stroke, the South African HIV Cancer Match study indicated that infection-related cancers (eg, cervical cancer, Kaposi sarcoma, and breast cancer) are common in PLWH. 33 Hence, the prevention and early detection of HIV-associated disease has become increasingly important in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of PLWH accessing ART worldwide are aging, and there is an increasing burden of a range of cancers among PLWH, even in the setting of declining cancer incidence rates 16,17 . Shifts toward aging‐associated cancers (eg, prostate, breast and colorectal cancers) have already been observed in countries with early introduction of ART, and the impact of aging on cancer risk in countries with younger populations of PLWH will become apparent in the coming years 18 …”
Section: International Patterns In Cancer Incidencementioning
confidence: 99%
“…16,17 Shifts toward aging-associated cancers (eg, prostate, breast and colorectal cancers) have already been observed in countries with early introduction of ART, and the impact of aging on cancer risk in countries with younger populations of PLWH will become apparent in the coming years. 18 Large studies of PLWH followed over time are critical to quantify cancer incidence and mortality trends, and to understand what is driving cancer risks and outcomes to identify means of prevention and optimize treatment. Data linkages with records from data warehouses, disease registries, cohort studies and serial cross-sectional studies T A B L E 1 Cancer sites for which HIV is considered by IARC in 2009 to be a carcinogen with "sufficient" or "limited" evidence.…”
Section: International Patterns In Cancer Incidencementioning
confidence: 99%